Validation of a method for quantifying enzalutamide and its major metabolites in human plasma by LC–MS/MS. (March 2014) - Bennett, Daniel; Gibbons, Jacqueline A; Mol, Roelof; Ohtsu, Yoshiaki; Williard, Clark
Background: Enzalutamide is an androgen receptor inhibitor that targets multiple steps in the androgen receptor signaling pathway. Oral enzalutamide was recently approved by the US FDA and health authorities in other regions for the treatment of patients with metastatic castration-resistant prostate cancer who previously received docetaxel. The objective of this study was to validate a method for quantification of enzalutamide and its two major metabolites in human plasma.Results: The analytes were extracted from plasma by an LLE procedure, separated by reversed phase HPLC and detected by MS/MS in positive mode ESI. The quantitation range was 0.0200–50.0 µg/ml.Conclusion: The method proved to be rapid and simple, and met FDA validation criteria.